EFFECT OF NITROGEN APPLICATION LEVELS ON GROWTH OF RICE UNDER DROUGHT STRESS CONDITIONS - Thiem, Tran; Akira, Yamauchi (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
The aim of this study was to investigate effects of nitrogen (N) application on root system development, photosynthetic rate and dry matter production under different drought stress conditions. The experiments were conducted in a line source sprinkler system creating a soil moisture gradient under a rain-out shelter.Three N fertilizer treatments were applied: 60, 120 and 180 kg N ha-1. Nitrogen fertilizer was mixed well with phosphorus and potassium fertilizer at the rate of 50 kg (P and K) ha-1and applied as basal dressing at 8 days after transplanting. The obtained results showed that increase of N level from 60 to 120 kg N ha-1increased total root length and shoot dry weight of Nipponbare under severe drought stress conditions (<17% w/w of soil moisture content (SMC)) but did not increased those traits as increased N application from 120 to 180 kg N ha-1. However, under mild drought stress (17-25% w/w of SMC) and well-watered (>25% w/w of SMC) conditions, total root length increased with increased N application leading to increase stomatal conductance and photosynthetic rate, and eventually increased shoot dry weight. In addition, only under well-watered conditions the relationship between the total root length and shoot dry weight was positive and notably significant at 120 and 180 kg N ha-1levels but not at 60 kg N ha-1level. The experiment suggested that the nitrogen application levels of 120 and 180 kg N ha-1increased the dry matter production due to the increased total root length under well-watered conditions.